EFISIENSI WAKTU FERMENTASI DAN VARIASI BRIX TERHADAP HASIL AKHIR KADAR DAN VOLUME BIOETANOL PADA LIMBAH GULA (MOLASSES): EFFICIENCY OF FERMENTATION TIME AND BRIX VARIATION ON FINAL RESULTS AND VOLUME OF BIOETHANOL IN WASTE SUGAR (MOLASSES) - Rizki Septiawan; Tri Rachmanto; Nurpatria (Energy, Materials and Product Design, 2024)
ABSTRACT The use of fossil fuels in everyday life is increasing. Fossil fuels that come from elements of living things that have been buried for thousands or even millions of years are non-renewable or non-renewable, so the more use of fossil fuels the longer the time will run out. Therefore, bioethanol can act as a substitute or alternative energy to reduce the use of fossil fuels. Bioethanol is a liquid resulting from sugar fermentation from a carbohydrate source (cellulose) using microbes. The purpose of this study was to determine the efficiency of fermentation time on the final yield of bioethanol content and volume from bagasse (molasses) using various Brix values â€‹â€‹of 14%, 15%, and 16% and the fermentation time used was 36 hours, 48 â€‹â€‹hours, and 60 hours. From the variation of Brix value and fermentation time, 9 kinds of treatment were obtained with 3 repetitions so that the total sample was 27. The results of this study indicate that the fermentation time factor is the dominant factor in determining the volume of alcohol, and the Brix factor is the dominant factor in determining the concentration. The most optimal treatment to produce the highest volume of alcohol was the 14% Brix variation with a 36-hour fermentation time variation with an average bioethanol volume of 1145.3 mL, and the most optimal treatment to produce high alcohol content was 16% Brix variation with an average the moderate alcohol content is 84%.   Keywords: Bioethanol, Molasses, Brix, Time efficiency, Fuel